2019
DOI: 10.1097/coc.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Nuclear Factor Kappa B Expression in Locally Advanced Cervical Cancer Patients Treated Definitively With Concurrent Chemoradiation

Abstract: Objectives: Nuclear factor kappa B (NFkB) is a transcription factor shown to confer treatment resistance in tumors. A previous report suggested an association between pretreatment NFkB and poorer outcomes for cervical cancer patients treated with chemoradiation therapy (CRT). We aimed to validate their findings in a larger patient cohort. Materials and Methods: This Institutional Review Board approved study included patients with locally advanced cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that NF-κB is a key factor to confer drug resistance in human cancer ( 61 ). The cytoplasmic NF-κB expression is correlated with a trend toward poor outcomes in locally advanced cervical cancer patients after chemoradiation therapy ( 62 ). Our results demonstrated that quercetin combined with cisplatin has a synergistic effect on cervical cancer, leading to decreased protein expression of EGFR, MYC, CCND1, and ERBB2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that NF-κB is a key factor to confer drug resistance in human cancer ( 61 ). The cytoplasmic NF-κB expression is correlated with a trend toward poor outcomes in locally advanced cervical cancer patients after chemoradiation therapy ( 62 ). Our results demonstrated that quercetin combined with cisplatin has a synergistic effect on cervical cancer, leading to decreased protein expression of EGFR, MYC, CCND1, and ERBB2.…”
Section: Discussionmentioning
confidence: 99%
“…16 Subsequent studies have revealed that TLR2/4/ 9 expression shows positive correlations with progression. [17][18][19] Altoos et al 20 demonstrated that the expression level of NF-κBp65 is associated with poor clinical outcomes in patients with locally advanced cervical cancer. Another study revealed that the expression of C-myc and POU5F1B is higher in CIN grade 2 or worse (CIN2+) than in normal patients or CIN1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the c‐MET gene was found to be a potent proto‐oncogene for hepatocyte growth and regeneration. A previous study demonstrated that c‐MET gene expression affects and contributes to the expression of important downstream genes and their pathways, such as NFκB, BCR/ABL and p‐STAT‐3 [28].…”
Section: Discussionmentioning
confidence: 99%